Low-level EMF effects on wildlife and plants: What research tells us about an ecosystem approach - Levitt, B. Blake; Lai, Henry C.; Manville, Albert M. (Frontiers in Public Health, 2022)
There is enough evidence to indicate we may be damaging nonhuman species at ecosystem levels across all taxa from rising background levels of anthropogenic non-ionizing electromagnetic fields (EMF). The focus of this paper is on the unique physiology of nonhuman species, their tremendous sensitivity to natural EMF, and the likelihood that artificial EMF in the extremely low frequency (ELF) and radiofrequency (RF) ranges of the nonionizing spectrum are capable at very low intensities of adversely affecting both fauna and flora in all species studied. Any existing exposure standards are for humans only; wildlife is unprotected, including within the safety margins of existing standards, which are inappropriate for trans-species sensitivities and different nonhuman physiology. Mechanistic, genotoxic, and potential ecosystem effects are discussed.